Definitions and scientific context of the Science of Commodities - BURDA, Alexandru; CHIRIMBU, Sebastian (Annals of Spiru Haret University. Economic Series, 2015)
The Science of Commodities as an independent discipline studies the level of satisfaction of implicit and explicit needs through quality and assortment of goods. In time, this scientific area has held various names. The best known of these names is the "Commodities". The term "Commodities" is equivalent in Romanian with "study (science) goods". The phrase "knowledge goods" was borrowed from Italian, which was formed from the Latin expression mercis (= the commodity) and Greek expression λογοξ, logos (= science, knowledge) deeper, state, Commodities that name comes from the Latin word MERX, which is mercis genitiv.